The Role of Women in Political Contestation in Indonesia: An Analysis of the Political Ideas of Ali Abdur-Raziq - Mahendra, Moh. Lutfi (Prodi Studi Agama-Agama, 2024)
This article discusses the potential of women in political contestation from the perspective of Ali Abdur Raziq, a leading Islamic thinker and reformer. The growth of the population, which is dominated by women, makes them a force in their own right. However, awareness of women's contributions to politics is still minimal. This view is supported by historical facts which show men as characters who dominate all aspects of life, so that narrating women and politics in the same conversation is almost considered something taboo. The purpose of writing this article is to re-present women as figures who stand the same as men, having the same opportunities in every matter. By using literature research, this article hypothesizes that women, while still carrying their religious awareness, have the potential to help change the country and society's views through political aspects